Relationship between Restorative Practices and School Climate at Secondary Level District Lahore - Kausar, Fahd Naveed; Ghaffar, Zareen; Jan, Shahida (Pakistan Journal of Humanities and Social Sciences, 2023)
The purpose of the study was to explore and compare the relationships between RPs and SC. The population consists of all public (male/female) and private (male/female) secondary school systems with 10 or more branches in the Lahore district. Multistage sampling techniques were used. The researcher used the cluster sampling approach to split the entire population into five groups (Tehsils). By using the stratified sampling approach, the researcher was able to identify two groups of strata: public/private, as well as male/female. From the private sector, a sample consisting of five male and five female schools from each tehsil in Lahore was selected. 520 teachers as a sample were selected. A questionnaire was used as a data collection tool. The researcher used both descriptive and inferential statistics. The findings revealed a strong positive relationship between restorative practices and school climate, there is no significant difference between RPs and SC of public and private schools and there is a significant difference between RPs and SC of male and female. For future research, it recommended that Schools should invest in training and resources to effectively implement RPs, which can promote a more inclusive, supportive, and positive SC.